A Multifaceted Quality Improvement Programme to Improve Acute Kidney Injury Care and Outcomes in a Large Teaching Hospital. Issue 1 (25th May 2017) - Ebah, Leonard; Hanumapura, Prasanna; Waring, Deryn; Challiner, Rachael; Hayden, Katharine; Alexander, Jill; Henney, Robert; Royston, Rachel; Butterworth, Cassian; Vincent, Marc; Heatley, Susan; Terriere, Ged; et al.
Abstract : Acute kidney injury (AKI) is now widely recognised as a serious health care issue, occurring in up to 25% of hospital in-patients, often with worsening of outcomes. There have been several reports of substandard care in AKI. This quality improvement (QI) programme aimed to improve AKI care and outcomes in a large teaching hospital. Areas of documented poor AKI care were identified and specific improvement activities implemented through sequential Plan-Do-Study-Act (PDSA) cycles. An electronic alert system (e-alert) for AKI was developed, a Priority Care Checklist (PCC) was tested with the aid of specialist nurses whilst targeted education activities were carried out and data on care processes and outcomes monitored. The e-alert had a sensitivity of 99% for the detection of new cases of AKI. Key aspects of the PCC saw significant improvements in their attainment: Detection of AKI within 24 hours from 53% to 100%, fluid assessment from 42% to 90%, drug review 48% to 95% and adherence to nine key aspects of care from 40% to 90%. There was a significant reduction in variability of delivered AKI care. AKI incidence reduced from 9% of all hospitalisations at baseline to 6.5% (28% reduction), AKI related length of stay reduced from 22.1 days to 17 days (23% reduction) and time to recovery (AKI days) 15.5 to 9.8 days (36% reduction). AKI related deaths also showed a trend towards reduction, from an average of 38 deaths to 34 (10.5%). The number of cases of hospital acquired AKI were reduced by 28% from 120 to 86 per month. This study demonstrates significant improvements related to a QI programme combining e-alerts, a checklist implemented by a nurse and education in improving key processes of care. This resulted in sustained improvement in key patient outcomes.